The Technique of Binary Code Decompilation and Its Application in Information Security Sphere - M. O. Shudrak; I. A. Lubkin; V. V. Zolotarev (Безопасность информационных технологий, 2012)
The authors describes a new technique of binary code decompilation and its application possibility in information security such as software protection against reverse engineering and code obfuscation analyze in malware.